1996
DOI: 10.1002/etc.5620150703
|View full text |Cite
|
Sign up to set email alerts
|

A limitation of the microtox® test for toxicity measurements of nonionic surfactants

Abstract: Abstract-The Microtox" test was successfully used to measure EC50 values of nonionic polyethoxylate surfactants. However, toxicity measurements of real samples that contain surfactants above a particular concentration, termed the critical toxicity concentration (CTC) are not valid. These samples require dilution before the test is performed, and because the relationship between toxicity and concentration is not linear above the CTC, the EC50 cannot be extrapolated back to give the toxicity of the original conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…CTC values were consistently lower than the CMC values for all surfactants although they are of the same magnitude. This was also observed by Sherrard et al [2]. These authors indicated that an association between surface tension and toxicity of the surfactant existed and they concluded that the non-micellar molecules produce a concentration-related toxic response.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…CTC values were consistently lower than the CMC values for all surfactants although they are of the same magnitude. This was also observed by Sherrard et al [2]. These authors indicated that an association between surface tension and toxicity of the surfactant existed and they concluded that the non-micellar molecules produce a concentration-related toxic response.…”
Section: Resultssupporting
confidence: 70%
“…The concentration at this point is termed as the Critical Toxicity Concentration (CTC) and the proportionality between log Γ and concentration no longer holds beyond this point. The curve plateaus beyond this point [2].…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…It is also possible that the surfactant itself has contributed to the increased toxicity, something that has been observed in an earlier study where the nonionic surfactant sodium dodecyl sulfate gave a toxic response in concentrations much lower than those utilized in the present study (Mazidji et al 1992). It is likely that the toxicity is a result of the very low surface tension, which implies damage to cell functions of the microorganisms (Sherrard et al 1996). In the present study, the concentration of surfactant was well above the CMC, and consequently, the surface tension was very low and could possibly explain the differences in Microtox® data observed between treatments receiving surfactant and those who did not.…”
Section: Ecotoxicological Characterizationmentioning
confidence: 63%